2020
DOI: 10.3389/fpsyt.2020.00833
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Slow Neural Processing, Developmental Differences and Sensitivity to Cannabis Effects in a Sample at Clinical High Risk for Psychosis From the NAPLS Consortium Assessed With the Human Startle Paradigm

Abstract: Biomarkers are important in the study of the prodromal period of psychosis because they can help to identify individuals at greatest risk for future psychotic illness and provide insights into disease mechanism underlying neurodevelopmental abnormalities. The biomarker abnormalities can then be targeted with treatment, with an aim toward prevention or mitigation of disease. The human startle paradigm has been used in translational studies of psychopathology including psychotic illness to assess preattentive in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…There are a small number of studies that found no difference between SCZ and CON subjects (24,(31)(32)(33). Slower latency at baseline predicted which adolescent and young adult subjects at high risk for developing SCZ went on to convert to psychosis over a 2-years period in a multisite study of prodromal SCZ (34). Importantly for the current paper, latency was slower in TOXO seropositive than seronegative subjects, and this finding was evident both in SCZ and CON subjects in the cohort (35).…”
mentioning
confidence: 53%
“…There are a small number of studies that found no difference between SCZ and CON subjects (24,(31)(32)(33). Slower latency at baseline predicted which adolescent and young adult subjects at high risk for developing SCZ went on to convert to psychosis over a 2-years period in a multisite study of prodromal SCZ (34). Importantly for the current paper, latency was slower in TOXO seropositive than seronegative subjects, and this finding was evident both in SCZ and CON subjects in the cohort (35).…”
mentioning
confidence: 53%
“…Cadenhead [46] found that a small sample of CHR-C had greater PPI than CHR-NC. Since 2019, Cadenhead et al [64] have published on a larger cohort from the NAPLS2 sample and did not find any PPI differences between CHR-C and CHR-NC but, within the CHR-C sample, age was significantly correlated with PPI (greater with advancing age and not typical of normally developing adolescents), replicating a previous age finding [46], that provided evidence of neurodevelopmental differences in the sample who later converted to psychosis. In addition, the startle response latency, a measure of neural processing speed, was greater in CHR-C compared to CHR-NC, with greater predictive power than clinical symptoms in predicting future psychosis in female CHR.…”
Section: Biomarkers Linked To Psychotic Conversionmentioning
confidence: 71%
“…Dickins et al [107] used a machine learning approach to develop a model using serum lipids and was able to differentiate CHR-C from CHR-NC groups. Cadenhead et al [64] added startle response latency to the clinical symptoms used in the NAPLS Psychosis Risk Calculator and found that in female CHR startle latency had a higher AUC than the clinical symptoms in predicting psychosis. Furthermore, Worthington et al [105] included salivary cortisol in the NAPLS Psychosis Risk Calculator and achieved a good C-index.…”
Section: Prediction Modelsmentioning
confidence: 99%